Production and Nutritive Value of Indigofera zollingeriana and Leucaena leucocephala in Peatland - Ali, A; Abdullah, Luki; Karti, P.M.D.H; Chozin, M.A.; Astuti, D.A. (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2014)
Abstract. This study was aimed to determine and compare the dry matter yield and nutrient content of Indigofera and Leucaena grown in peatland. This experiment was conducted in peatland type soil (type sapric) in Pekanbaru city, DM yield and nutrient contents data were analyzed by 2x3 factorial design with 3 replication. Two treatments compared were Indigofera zollingeriana (Indigofera) and Leucaena leucocephala (Leucaena). Indigofera was proven significantly higher than Leucaena in all harvest regarding dry matter (DM) of leaf and stem of 29.9% and 25%, respectively, crude protein (CP) of 23.1% and 17.6%, respectively. While neutral detergent fibre (NDF) and acid detergent fibre (ADF) content of Indigofera leaf (35.9% and 25.1%, respectively) was significantly lower than those of Leucaena leaf (40.9% and 29.3%, respectively). It was concluded that the production and nutritive value of Indigofera zollingeriana was superior to Leucaena leucocephala in peatland (type sapric). Key words: Legume tree, Sapric, nutrient content, In vitro digestibiliy Abstrak. Penelitian ini bertujuan menentukan dan membandingkan bahan kering dan kandungan nutrisi Indigofera dan Leucaena yang tumbuh di lahan gambut. Percobaan ini dilakukan di lahan gambut di Pekanbaru menggunakan pola faktorial 2x3 dengan ulangan 3 kali. Dua perlakuan yang dibandingkan adalah Indigofera zollingeriana (Indigofera) dan Leucaena leucocephala (Leucaena). Indigofera terbukti secara nyata lebih tinggi daripada Leucana di semua periode panen, berkaitan dengan kandungan BK (bahan kering) daun dan batang berturut-turut 29,9% dan 25%, dan protein kasar (PK) 23,1% dan 17,6%. sedangkan neutral detergent fibre (NDF) dan acid detergent fibre (ADF) daun indigofera berturut-turut 35,9% dan 25,1%, lebih rendah secara nyata daripada daun Leucaena, yaitu 40,9% dan 29,3%. Disimpulkan bahwa produksi dan nilai nutrisi Indigofera zollingeriana lebih tinggi dari Leucaena leucocephala di lahan gambut (jenis saprik) Kata kunci: Pohon legume, Saprik, Kandungan Nutrisi, Kecernaan in vitro